2020
DOI: 10.1016/j.joep.2020.102271
|View full text |Cite
|
Sign up to set email alerts
|

Family identification facilitates coping with financial stress: A social identity approach to family financial resilience

Abstract: Highlights• Financial research overlooks how family affects experiences of economic challenge.• We argue that family identification fosters support, promoting financial coping.• We provide evidence in support of this in two community surveys (N=369; N=187).• The result show how family cohesion can promote mental well-being/ resilience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 48 publications
8
31
0
Order By: Relevance
“…Essentially, the pandemic is about group psychology that entails community participation and engagement (Jetten et al 2020 ). Arguably, family identification and cohesion promote wellbeing and resilience (Stevenson et al 2020 ), which may have also positively impacted QoL. In large scale disasters, people are likely to define themselves in terms of their shared identity (Drury 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Essentially, the pandemic is about group psychology that entails community participation and engagement (Jetten et al 2020 ). Arguably, family identification and cohesion promote wellbeing and resilience (Stevenson et al 2020 ), which may have also positively impacted QoL. In large scale disasters, people are likely to define themselves in terms of their shared identity (Drury 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Debt is an indicator of resource deficiency and negatively associated with subjective wellbeing or positively associated with financial distress (Tay et al, 2017) and psychological distresses (Brown et al, 2005). In the research literature, factors are identified to help reduce distress or improve mental health such as financial capability (Taylor et al, 2011) and family financial efficacy (Stevenson et al, 2020). Researchers also find that positive financial behaviors such as making ends meet is an important mediator to help reduce financial worry (de Bruijn & Antonides, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Social identification is malleable and responsive to context and intervention (e.g., Haslam et al, 2019;Steffens et al, 2019). Both samples were, on average, ambivalent in their level of family identification and these levels were lower than in typical samples (e.g., Stevenson et al, 2020), suggesting family identification could be increased with targeted intervention. This represents a novel approach to family intervention that does not require change to trait-type constructs.…”
Section: Discussionmentioning
confidence: 89%
“…We suggest that identification with family is crucial to experiencing these health benefits. Outside the ED context, family identification has been associated with positive mental health outcomes for adolescents (Miller et al, 2017), those affected by financial distress (Stevenson et al, 2020), and those affected by intimate partner violence (Naughton et al, 2015). However, the degree to which family identification can reduce loneliness (and whether this is one of the mechanisms for its health benefits) has yet to be explored for PWED.…”
Section: Group Memberships Social Identities and Eating Disorder Rementioning
confidence: 99%